Eyes at the Back of His Head: Precarious Masculinity and the Modern Tracking Shot. Issue 1 (March 2015) - Barker, Jennifer M.; Cottrel, Adam
Abstract : This paper examines masculinity in relation to the modern tracking shot in Daren Aronofsky's The Wrestler (2008) and Derek Cianfrance's The Place Beyond the Pines (2012). These films make prominent use of a particular tracking shot in which the camera floats behind a male character, his head neatly centred in the frame. The camera in these 'follow-shots' seems unmistakably but loosely tethered to the character's body. This paper attempts to ascertain the phenomenological nature and critical significance of that relationship, which in recent films expresses the intimate distance and dissonance between mobile cameras, masculinity and the male body in the twenty-first century.